THE INFLUENCE OF GLASS CEILING PRACTICES TO WOMEN EMPLOYE IN BANK SULUTGO BRANCH BITUNG - Paruntu, Angel Alvamega; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Women in the world of work is already familiar. Indonesia should still follow traditional rule, the role of women in the world of work is still limited. Women are still considered inappropriate to men's ability to work. The work women do in Indonesia is still a lot in the areas of public services and their positions in the company only occupy the position of middle and lower managers, women have no power or certain rights in the company. The barrier is called Glass Ceiling. This research aims to know how is Glass Ceiling Practices influence women employee in Bank Sulut Go Branch Bitung. This research is using qualitative method. The sample size of this research is 10 womenÂ employee who work in PT. Bank SulutGo. The results showed that Glass ceiling does not affect women employee career development in Bank SulutGo Branch Bitung. So, related with the findings In order to avoid the action of glass ceiling or gender discrimination in the future (if there), Bank SulutGo have to make a seminar or observation every month in every branch offices about the disadvantage of glass ceiling and its influence to the company and organization.Keywords: glass ceiling